PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Zahari Afsih; Syahriani Sirait (Universitas Islam Sumatera Utara, 2026)
This study aims to analyse students’ ability to transform contextual problems into mathematical models in the subject of Systems of Linear Equations with Two Variables through the application of the Problem-Based Learning approach. This study employs a quantitative approach using a quasi-experimental method and a pretest-posttest control group design. The study population comprises all Year 8 secondary school students, whilst the sample consists of two classes an experimental class and a control class selected using purposive sampling. The research instrument consists of a test in the form of contextual story problems used to measure students’ mathematical modelling abilities. Research data were obtained through pre-tests, post-tests, student answer sheets, brief interviews, and the use of worksheets based on contextual problems. Data analysis was conducted using normality tests, homogeneity tests, t-tests, N-Gain, and effect size. The results of the study indicate that students who learn using the Problem-Based Learning model demonstrate better ability in transforming contextual problems into mathematical models compared to students who learn using conventional teaching methods. Consequently, the Problem-Based Learning model can serve as an effective alternative teaching method for enhancing students’ mathematical modelling skills.